Uncertainty-driven cooperation - Doruk Cetemen; Ilwoo Hwang; Ayça Kaya (Theoretical Economics, 2020)
We consider dynamic team production in the presence of uncertainty. Team members receive interim feedback that depends on both their current effort level and the project's uncertain prospects. In this environment, each member can encourage the others by making them more optimistic about the project's prospects. We study the extent to which this incentive counters the usual free-riding incentive. Restricting the agents' access to feedback can increase their equilibrium effort levels by mitigating the ratchet effect. In this case, using joint performance measures can be beneficial even when individual measures are available.
Keywords: C72; C73; D23; D83; 330; Team production; free-riding; uncertainty; learning